Evaluation of the mechanical behavior of 2001 LDSS and 2205 DSS reinforcements exposed to simultaneous load and corrosion in chloride contained concrete pore solution. (September 2020) - Briz, E.; Martin, U.; Biezma, M.V.; Calderon-Uriszar-Aldaca, I.; Bastidas, D.M.
Abstract: The present work is focused on the study and evaluation of the mechanical properties of the new low-nickel 2001 lean–duplex stainless steel (LDSS), 2205 duplex stainless steel (DSS) and B500SD carbon steel rebars, influenced by aggressive corrosion environment. Test specimens were loaded to 85% of the yield strength while simultaneously exposed to 8 wt% Cl − concrete pore solution for 315 days. Subsequently, the specimens were loaded until failure at a high deformation rate of 0.41 mm/s. The analysis of the stress‒strain curve showed a reduction of the ultimate tensile strength greater than 35% for the B500SD, while the 2001 LDSS and 2205 DSS show a reduction lower than 20% and 10%, respectively. Analyzing elongation to failure, neither 2001 LDSS nor 2205 DSS show evidence of stress corrosion under the simultaneous action of chlorides and load. The toughness change in the 2205 DSS is negligible, the 2001 LDSS slightly reduces its resilience, and the B500SD severely decreases both properties. The fractography study revealed that 2001 LDSS and 2205 DSS show a dimple pattern with features of ductile fracture by coalescence of microvoids. Highlights: Mechanical properties of 2001 LDSS and 2205 DSS rebars under load and corrosion, suggest viability in harsh environment. 2001LDSS: ultimate strength and elongation at ultimate strength decrease 19% and 25%. 2205DSS: ultimate strength decreases 6%. Fracture toughness reduction: 7% for 2001 LDSS vs. 2205 DSS, and 23% for B500SD vs. 2001LDSS.